Production of chipped stone atrifacts on the late Neolithic and Copper Age site Slavča, Croatia - Šošić, Rajna (2006)
Little is known about the process of production and usage of the artifacts during the Neolithic and late prehistoric periods in Croatia. In the past few years, researches on the chipped stone artifacts begun to step up. This paper presents the results of the technological and typological analysis of the chipped stone assemblage from the site of Slavča, in the Croatian region of Western Slavonia. The site was inhabited during the final stages of Neolithic (Sopot Culture), and throughout the Copper Age (Lasinja and Kostolac culture). There is resemblance in the techniques of production (in both periods indirect percussion was used for producing blades), as well as in the ways of the production of flakes and in tool typology. There are strong differences in the procurement of the raw material and the process of the production of blades between these two periods. This paper aims to elaborate the settlement and mobility patterns of populations that settled on Slavča throughout the analysis of the lithic assemblage.
Projekt MZOS
ENG